Reduction of Sb(V) by coupled biotic-abiotic processes under sulfidogenic conditions. Issue 2 (February 2021) - Johnson, Clayton R.; Antonopoulos, Dionysios A.; Boyanov, Maxim I.; Flynn, Theodore M.; Koval, Jason C.; Kemner, Kenneth M.; O'Loughlin, Edward J.
Abstract: Increasing use and mining of antimony (Sb) has resulted in greater concern involving its fate and transport in the environment. Antimony(V) and (III) are the two most environmentally relevant oxidation states, but little is known about the redox transitions between the two in natural systems. To better understand the behavior of antimony in anoxic environments, the redox transformations of Sb(V) were studied in biotic and abiotic reactors. The biotic reactors contained Sb(V) (2 mM as KSb(OH)6 ), ferrihydrite (50 mM Fe(III)), sulfate (10 mM), and lactate (10 mM), that were inoculated with sediment from a wetland. In the abiotic reactors, The interaction of Sb(V) with green rust, magnetite, siderite, vivianite or mackinawite was examined under abiotic conditions. Changes in the concentrations of Sb, Fe(II), sulfate, and lactate, as well as the microbial community composition were monitored over time. Lactate was rapidly fermented to acetate and propionate in the bioreactors, with the latter serving as the primary electron donor for dissimilatory sulfate reduction (DSR). The reduction of ferrihydrite was primarily abiotic, being driven by biogenic sulfide. Sb and Fe K-edge X-ray absorption near edge structure (XANES) analysis showed reduction of Sb(V) to Sb(III) within 4 weeks, concurrent with DSR and the formation of FeS. Sb K-edge extended X-ray absorption fine structure (EXAFS) spectroscopy analysis indicated that the reduced phase was a mixture of S- and O-coordinated Sb(III). Reduction of Sb(V) was not observed in the presence of magnetite, siderite, or green rust, and limited reduction occurred with vivianite. However, reduction of Sb(V) to amorphous Sb(III) sulfide occurred with mackinawite. These results are consistent with abiotic reduction of Sb(V) by biogenic sulfide and reveal a substantial influence of Fe oxides on the speciation of Sb(III), which illustrates the tight coupling of Sb speciation with the biogeochemical cycling of S and Fe. Abstract : Antimony; Biogeochemistry; Dissimilatory sulfate reduction; Microbial reduction; Iron sulfide